The biochemistry and physiology of different hybrid and grafted eggplants in response to NaCL salinity in soil and hydroponic systems - Panagiotakis, Giorgos D. (Cranfield University, 2013)
The major problem of salinity n regions of intensive cultivations such as Ierapetra, has started to affect the crop production. This project was designed to study the effects of salinity on several biochemical and physiological parameters in two hybrids of eggplant as grafted and non-grafted. The two hybrids were the Solanum melongena L hybrid Habana and Solanum melongena L hybrid Vernina. The concentrations that were chosen (12.5 25, 50, 100, 150 and 200mM) represent a scale of salt concentration and were cultivated as self rooted plants in soil, hydroponically and hydroponically as grafted. Grafting also seems to play an important role for salinity tolerance. To corroborate the different parameters were used as indicators of salinity affection and quantified. Plant height and number of leaves were affected in all three experiments and for all plant types whether grafted or not. Similar were the results for the dry and fresh weight of stem leaves and fruits. For the physiological function of the plants factors such as chlorophyll fluorescence and photosynthetic rate were affected especially at higher concentrations of NaCL. The chlorophyll content in the leaves, which was also measured, was negatively affected in all hybrids. Biochemical measurements the K and Na concentrations in dry leaves and the enzyme activity of APX, GPX and SOD were also made. The K and Na ion concentrations were similar with other studies presenting a reduction of K and raise of Na as the concentration of salt was rising. Unfortunately the enzyme activity was not affected at the specific experiment so it was not able to find exactly how the salinity affects this factor. Overall the results of grafted plants were better than as self rooted and the Solano torvum plant used as rootstock is more tolerant than the Tomato Resistar also used as rootstock.